Research on the Load Bearing and Impact Resistance of a Novel Structure Exhibiting Both Positive and Negative Poisson’s Ratios - Zhang, Xidong; Cui, Hongyu; Hu, Haoming; Yin, Xiaokai; Xu, Huanqiu (Shock and Vibration, 2024)
A ship equipment pedestal is a structure that connects power equipment to a hull. It must have a high load-bearing capacity and the ability to withstand large impact loads. In this paper, a novel structure with a positive-negative Poisson’s ratio is proposed. The deformation mechanism and mode of this structure under quasistatic compression loading are analysed via numerical simulation. Based on this new structure, a multicellular pedestal is designed, and its bearing capacity and impact resistance are analysed. The structural parameters of the pedestal are optimized. An experiment is conducted to evaluate the impact resistance of the pedestal model, which confirms that the proposed multicellular pedestal exhibits excellent impact resistance.